Adopsi Inovasi Mengolah Lahan Tanpa Bakar Oleh Masyarakat di Kabupaten Rokan Hilir - Mujayana, Endang; Rosnita, Rosnita; Andriani, Yulia (Journal of Agribusiness and Community Empowerment, 2020)
This research aims to know what the extent to which the community adopted the innovation of processing land without burning and what stages of cultivation without burning by people of Rokan Hilir Riau Province. The research method used was survey method and in-depth analysis using questionnaires with primary and secondary data. The respondents in this research as many as 15 people consisting of a society that has already adopted the innovation of processing land without burning and the Government as well as Society of Fire Care (SFC) in the village of Rantau Bais Sub-district of Tanah Putih and Labuhan Tangga Kecil village Sub-district Of Bangko Regency of Rokan Hilir. The determination of community respondents used snowball sampling and purposive sampling for institutional respondents. The analysis of the data used for the purposes of the adoption process innovation to cultivate land without burning, namely Scales Likerts analysis and descriptive analysis is used to find out land processing system without burning have done by the community. Research results showed that land without burning processing system which conducted the community consist of several stages in the form of clearing or logging and spraying, and buildup and allowed to decay naturally. The rate of adoption of innovation of processing land without burning in the Rokan Hilir has thehigh categorywith value score 3.52. The high adoption process innovation of processing land without burning is due to the high level of knowledge, decision and implementation that also have been good. The decision to adopt was high because the society doing processing in terms of plant maintaining plants and plantations.